2017
DOI: 10.2298/gsf1715167z
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of LVL composed of poplar and beech veneer and possibilities of their application for window frames

Abstract: Извод: Предмет овог рада је испитивање физичких и механичких својстава тополових LVL плоча споља додатно ојачаних буковим фурниром, као и испитивање чврстоће угаоних елемената везе за прозор израђених од овог материјала. Плоче су пресоване сувим врућим поступком у индустријским условима, а као везивно средство коришћен је FF фенол-формалдехидни лепак. Узорци за испитивање чврстоће угаоних спојева спајани су двоструким призматичним чепом и прорезом помоћу PVA-ц лепка класе D4. Статистичка анализа показала је да… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The results of corner window frame double tenon glue joint strength produced from combined PF bonded poplar-beech veneer LVL showed that torque was 2 to 3 times higher than with window frames produced from spruce solid wood. This indicates that LVL composed of poplar veneers in core layers, and only outer layers of beech veneers have good potential (Zdravković et al 2017). The impact bending strength (IBS) of laminated veneer lumber (LVL) varies depending on the wood species used.…”
Section: Mixed Hardwood Lvlmentioning
confidence: 99%
“…The results of corner window frame double tenon glue joint strength produced from combined PF bonded poplar-beech veneer LVL showed that torque was 2 to 3 times higher than with window frames produced from spruce solid wood. This indicates that LVL composed of poplar veneers in core layers, and only outer layers of beech veneers have good potential (Zdravković et al 2017). The impact bending strength (IBS) of laminated veneer lumber (LVL) varies depending on the wood species used.…”
Section: Mixed Hardwood Lvlmentioning
confidence: 99%
“…In order to increase the use of poplar wood in construction, its mechanical properties are improved through lamination, that is, the formation of veneer-based products in the form of plywood and LVL panels. The improvement of the mechanical properties of these products is also tested by combining poplar veneer with veneers of other types of wood [5][6][7] or with some other synthetic materials. Engineering wood products based on poplar veneers and composite materials have great potential for structural use [8].…”
Section: Introductionmentioning
confidence: 99%